ANALISIS SISTEM TATANIAGA KARET PADA PETANI KARET EKS UPP TCSDP DI DESA BALAM MERAH KECAMATAN BUNUT KABUPATEN PELALAWAN - Sarah Fidelia Situmorang; Ahmad Rifai; evi Maharani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to analyze  the marketing channel, marketing margin, and marketing efficiency of rubber on smallholder plantation of ex-UPP TCSDP. Research also analyzes the market structure and price transmition elasticity of rubber product (ojol) at Balam Merah Village. This research is using the survey method. Data was collected on 30 smallholders rubber plantation by purposive sampling technique, 6  the village merchant, and 3 the wholesaler by snowball sampling technique. The research results shows there are two rubber marketing channels which are  farmers - wholesalers - factory, and farmers - village merchant – wholesaler - factory.  The value of marketing margin on the first marketing channel as Rp. 928,21/kg , and is more efficient than the second marketing  channel (11,23 percent).   Keywords : UPP TCSDP, Marketing, Margin, Efficiency, Price Transmission.